Eksperimen Pembelajaran Matematika Dengan Pendekatan Kontekstual dan Pendekatan Saintifik Terhadap Hasil Belajar Matematika Ditinjau Dari Motivasi Siswa Kelas VIII SMP Al-Islam Kartasura Tahun Ajaran 2016/2017 - Larasati, Dewi, Masduki,S.Si, M.Si, Sri Rejeki,S.Pd,M.Pd (2017)
The aim of this study is to find out: (1) the different effect of Contextual approach and Scientific approach to the mathematics learning outcomes, (2) the different effect of motivation level to the mathematics learning outcomes, (3)the effect of interaction between learning approaches and motivation level to the mathematics learning outcomes. This research is an experimental research with quasi-experiment design. Population of this research are all of the 8th grade students in SMP Al-Islam Kartasura with school year 2016/2017. The sample of this research are two class. Sample technic in this research is cluster random sampling. Data collection technic are test and documentation method. Data analysis technic is variant two ways analysis with differet cell. Significant degree is  =5%. According of the hypothesis testing, the conclusion are:(1) there are different effects of contextual approach and scientific approach on mathematics learning outcomes.(2) there are different effects level of motivation on mathematics learning outcomes. (3) there is no effect of interaction between of approach and motivation for mathematics learning outcomes.